The Effect of Flash Sale and Free Shipping on Repurchasing Interest through Customer Experience in the Shopee App in South Jakarta - Rahayu Lestari; Mardin Rachman (Budapest International Research and Critics University, 2022)
This study aims to analyze the effect of flash sales and free shipping on repurchase intentions through customer experience on the Shopee Application in South Jakarta. Sources and research data using primary data in the form of a questionnaire, this research data was given to 96 respondents. The research sample was taken using purposive sampling. The analytical method used is Partial Least Square (PLS) with the help of the SmartPLS 3.0 application. Partial research results with the conclusion that flash sale has a positive and significant effect on customer experience, free shipping has a positive and significant effect on customer experience, and customer experience has a positive and significant effect on repurchase interest in the Shopee Application.